Advancing therapeutic discovery through phenotypic screening of the extracellular proteome using hydrodynamic intravascular injection. (1st November 2014) - Baribault, Helene; Majeti, Jiangwen Z; Ge, Hongfei; Wang, Jinghong; Xiong, Yumei; Gardner, Jonitha; Yang, Li; Gupte, Jamila; Gong, Yan; Pan, Zheng; Cutler, Gene; Kassner, Paul; et al.
Abstract : Objective: Although the human genome encodes ∼ 20, 000 protein-coding genes, only a very small fraction of these have been explored as potential targets for therapeutic development. The challenge of identifying and validating new protein targets has contributed to the significant reduction in the productivity of the pharmaceutical industry in the recent decade, highlighting the continued need to find new therapeutic targets. Research design and methods: The traditional methods to discover new targets are expensive, low throughput and time consuming, usually taking years to validate or invalidate a target. To address these limitations, as a proof of concept, we explored the hydrodynamic tail vein (HTV) injection as a gene delivery method for direct in vivo phenotypic screening of novel secreted factor targets for Type II diabetes therapeutics. Results: High levels and sustained expression of target proteins were observed in diabetic mouse models tested, allowing us to identify multiple novel hormones that may regulate glucose metabolism. Conclusions: These results suggest that HTV is a low-cost, high-throughput method for direct in vivo phenotypic drug screening in metabolic disorders and could be applicable to many other disease areas as well. This method if combined with other approaches such as human genetic studies could provide a significant value to future drug discovery.